Partnership and Cooperation Agreement between the Russian Federation and the European Union 1994 (PCA): Perjanjian Kemitraan dan Kerja Sama antara Federasi Rusia dan Uni Eropa 1994 (PCA) - Al-Sabawi, Mohammed Hamid Hamad; Al-Rifai, Lubna Riyadh Abdulmajid (Academia Open, 2026)
General Background: The post–Cold War international system created new frameworks for cooperation between major actors. Specific Background: The 1994 Partnership and Cooperation Agreement between the Russian Federation and the European Union established a legal and institutional basis for political dialogue, economic cooperation, and coordination. Knowledge Gap: Limited understanding exists regarding how such legal frameworks function in practice and their ability to sustain long-term strategic partnerships under changing geopolitical conditions. Aims: This study analyzes the origins, provisions, and outcomes of the agreement using historical and analytical methods. Results: The findings show that the agreement successfully structured bilateral relations, institutionalized dialogue, and supported economic interaction, but failed to achieve a comprehensive strategic partnership due to conflicting interests and external pressures. Novelty: The study combines historical context with analytical evaluation to assess both the strengths and structural limitations of the agreement. Implications: The results highlight the complexity of sustaining international partnerships and provide insights into the evolving nature of EU–Russia relations in a dynamic global system. Keywords: Partnership Agreement, EU Russia Relations, International Cooperation, Political Dialogue, Economic Integration Key Findings Highlights Institutional mechanisms established for continuous bilateral engagement Long-term cooperation maintained despite shifting geopolitical conditions Strategic alignment constrained by competing national interests